New product strategy: Key characteristics that distinguish leading innovators in selected large South African manufacturing industries - Theresa-Anne Davies (South African Journal of Business Management, 1997)
Product innovation has to be universally recognized as a central strategy for building market share and securing business success. The purpose of this exploratory research study was to attempt to identify key characteristics that distinguish leading innovators in selected South African Industries. Based on the findings from both the qualitative and quantitative studies, a profile emerges of successful companies that appears to distinguish them from less successful companies, and some guidelines are suggested in terms of the types of strategies that appear to be effective, the type of leadership required, and the skills needed to get product development undertaken successfully. One of the most interesting findings from the research is the observation that the large South African companies surveyed are not very innovative. The study concludes with some recommendations for further research into the strategic factors that contribute to innovation success.
Keywords: 650